Botani Hutan Di Hutan Hujan Tropis Dataran Rendah PT.Silva Gama Jambi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ADSTRACT A botanical study on lowland tropical rain forest was conducted at Silva Crania forest concession in Jambi. The objective of the study was mainly to understand the species composition of the logged over area forest. To achieve the goal of the study two separate permanent plots of 100 x 100 m each were established and all trees within the permanent plots with diameter of 5 cm and up were enumerated. Field characters of each species were recorded and herbarium specimen were collected. Identification was conducted at the Laboratory of Dendrology, Faculty of Forestry, Gadjah Mada University, Yogyakarta by using reference Tree Flora ofMalaya. In some cases the herbarium specimen were identified by comparing with herbarium materials, housed in Herbarium Bogoriense, Bogor. Result of the study showed that there were 42 families found in the area and among these was the Burseraceae family. The Family of Burseraceae was to consist of 11 species in the area namely : Canarium littorale BL, C. megalanthurn Merrill, C pseudosumatranum Leenhouts, Dacryodes costata (Bennet) Lam, D. incurvata (Engler) Lam, D. Laxa (Bennet) Lam, D. macrocarpa (King) Lam, D. puberula (Bennet) Lam, D. rugosa (B1.) Lam, Santiria conferta Bennet and S. tomentosa BL Each species was described and illustrated. In addition, a key for identification based on field characters was provided as well. The number of species of the Burseraceae family found in the studied area revealed to be far less than that of listed in Check list of Tree Flora ofSumatra. In this list the number of species of this family come up to 33 spp. The presence of the Burseraceae species in the forest was paramount important as most of the species provide useful] food for wilders.